MiR-155-Mediated Deregulation of GPER1 Plays an Important Role in the Gender Differences Related to Inflammatory Bowel Disease - Xiaojuan Shao; Jintao Li; Fumin Xu; Dongfeng Chen; Kaijun Liu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Aim. The incidence and clinical manifestations of inflammatory bowel disease (IBD) are thought to have gender differences, which suggests that the estrogen signaling pathway and intestinal flora may play key roles in the pathogenesis of IBD. In IBD, microRNA-155 (miR-155) is upregulated and regulates G protein coupled estrogen receptor (GPER1), which affects the intestinal flora. The objective of this study was to investigate the role of the estrogen receptors and miR-155 in the pathogenesis of IBD. Methods. From July 2018 to July 2019, in the Department of Gastroenterology at Daping Hospital, Army Military Medical University, a total of 50 patients with IBD were included in this study, and 24 healthy examinees were randomly selected as the control group. Colonoscopies were performed, and clinical characteristics and blood samples were collected from all of the subjects. The serum cytokine levels in the patients with IBD and the health donors were detected by ELISA, and the estrogen receptor level measurements for all of the participants were assessed by immunohistochemistry (IHC) and quantitative real-time PCR (qPCR). The miR-155 levels were detected by qPCR in all of the participants, and miR-155−/− mice were used to investigate the mechanism of miR-155 in the pathogenesis of IBD. Results. The clinical characteristics and medications were different for the IBD patients when gender was considered. The male patients produced more proinflammatory cytokines, and while GPER1 expression was downregulated, miR-155 was upregulated in the patients with IBD. MiR-155 showed proinflammatory activity, while GPER1 showed an anti-inflammatory response during the pathogenesis of IBD. The miR-155−/− mice showed improvements in weight loss, survival, rectal bleeding, colon length, and histopathological changes compared with the wild-type mice. Furthermore, the male miR-155−/− mice showed increased inflammation compared to the female miR-155−/− mice in the above aspects. Conclusion. This study presents evidence indicating that miR-155 plays a key role in the pathogenesis of IBD for the different genders. MiR-155 was upregulated and showed proinflammatory activity, whereas GPER1 showed an anti-inflammatory response during the pathogenesis of IBD. The results demonstrated that more proinflammatory cytokines and reduced GPER1 levels were observed in the male IBD patients. Thus, miR-155 was involved in the regulation of GPER1 and induced gender differences in IBD patients. MiR-155 may be a potential marker for IBD-targeted therapy.